In Vitro Activities of Caspofungin Compared with Those of Fluconazole and Itraconazole against 3,959 Clinical Isolates of Candida spp., Including 157 Fluconazole-Resistant Isolates - Pfaller, M. A. (American Society for Microbiology, 2003)
Caspofungin is an echinocandin antifungal agent with broad-spectrum activity against Candida and Aspergillus spp. The in vitro activities of caspofungin against 3,959 isolates of Candida spp. obtained from over 95 different medical centers worldwide were compared with those of fluconazole and itraconazole. The MICs of the antifungal drugs were determined by broth microdilution tests performed according to the NCCLS method using RPMI 1640 as the test medium. Caspofungin was very active against Candida spp. (MIC at which 90% of the isolates were inhibited [MIC(90)], 1 μg/ml; 96% of MICs were ≤2 μg/ml). Candida albicans, C. dubliniensis, C. tropicalis, and C. glabrata were the most susceptible species of Candida (MIC(90), 0.25 to 0.5 μg/ml), and C. guilliermondii was the least susceptible (MIC(90), >8 μg/ml). Caspofungin was very active against Candida spp., exhibiting high-level resistance to fluconazole and itraconazole (99% of MICs were ≤1 μg/ml). These results provide further evidence for the spectrum and potency of caspofungin activity against a large and geographically diverse collection of clinically important isolates of Candida spp.